Agenda Kebudayaan Baru Uni Eropa Pasca-Brexit dan Peningkatan Regionness: Karakter Kebijakan Kultural untuk Membangun Identitas Kolektif - Zulkhair Burhan (Journal of International and Local Studies, 2026)
This manuscript aims to explain the character of the European Union's post-Brexit cultural policy through the EU's New Cultural Agenda adopted by the European Commission in 2018, which is also a response to the weakening of regional cohesion marked by the strengthening of Euroskepticism politics. By using the concept of regionness Hettne and Soderbaum (2000) as an analytical framework to measure the degree of regional cohesion, it is explained that the EU's New Cultural Agenda has two main characteristics: policies that increasingly strengthen the role of civil society and policies that are inclusive and people-centered. These two characters, which are in line with the criteria of the Regional Community phase (active participation of civil society) and Region-State (policy decentralization) in the concept of regionness, open up opportunities to strengthen shared identity and a sense of belonging to the European Union.